Ekman transport : a trigger of interannual extreme formation rates of eighteen degree water - Li, Ke (HAL CCSD, 2020)
The North Atlantic subtropical gyre was shown to have experienced warming since 1970s. But this trend sits on top of a large interannual variability driven by mechanisms that are yet to be clarified, especially with regard to extreme winter events. In this research, we developed an observation-based ocean heat budget of the upper 800 m in the western subtropical North Atlantic, a region where heat is mostly stored in the Eighteen Degree mode Water (EDW).In interannual time scale, the variability of geostrophic advection, mostly driven by the GulfStream, is the most dominant factor to that of the ocean heat content (OHC) variability, 2.5 times as large as that of Ekman advection and almost four times as large as that of surface heat loss (which dominates at the seasonal cycle only). However, the annually ventilated EDW exhibits extreme values in 2008, 2013, and 2015 that correspond to opposite OHC anomalies. We will show that Ekman advection is the best indicator and driving mechanism explaining these extreme occurrences. We have further shown that such extreme Ekman advection patterns can be linked to large scale atmospheric weather storms and that both storm intensity and duration have an impact on the extreme of EDW ventilation and that of the heat content in the western subtropical North Atlantic. La gyre subtropical de l'Atlantique Nord montre depuis 1970 une tendance au réchauffement. Cette tendance se superpose à une variabilité interannuelle intense, mais dont les mécanismes ne sont pas encore bien connus, en particulier, à l'égard des évènements extrêmes hivernaux. Dans cette thèse, nous avons développé, sur la base d'observations, un bilan de chaleur océanique, au-dessus de 800m dans la région ouest subtropicale de l'Atlantique Nord, une région où la chaleur est presque entièrement stockée dans l'Eau Modale à 18oC (Eighteen Degree Water, EDW). A l'échelle de temps interannuelle, la variabilité de l'advection géostrophique est presqu' entièrement contrôlée par le Gulf Stream, qui est le facteur ...